1993
DOI: 10.1007/bf03188809
|View full text |Cite
|
Sign up to set email alerts
|

Steady state investigation of possible pharmacokinetic interactions of moxonidine and glibenclamide

Abstract: The aim of the study presented here was to determine possible pharmacokinetic interactions of moxonidine and glibenclamide at steady state in 18 healthy male volunteers. Multiple oral doses of 0.2 mg of moxonidine b.i.d. (q. 12 h) and of 2.5 mg of glibenclamide o.i.d. (q. 24 h) were administered alone and in combination in an open, non-randomized, three-treatment design. The preparations were given for 5 days in each of the 3 periods. The results of this multiple dose study did not indicate substantial pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Three studies were conducted to determine possible pharmacokinetic interactions between moxonidine and hydrochlorothiazide (1 30), digoxin (94), and glibenclamide (90). Co-administration of moxonidine did not significantly change the pharmacokinetics of digoxin and hydrochlorothiazide; nor did digoxin and hydrochlorothiazide alter the pharmacokinetics of moxonidine.…”
Section: Drug Interactionsmentioning
confidence: 99%
“…Three studies were conducted to determine possible pharmacokinetic interactions between moxonidine and hydrochlorothiazide (1 30), digoxin (94), and glibenclamide (90). Co-administration of moxonidine did not significantly change the pharmacokinetics of digoxin and hydrochlorothiazide; nor did digoxin and hydrochlorothiazide alter the pharmacokinetics of moxonidine.…”
Section: Drug Interactionsmentioning
confidence: 99%
“…In addition, several studies demonstrate the absence of any interaction between glibenclamide and pirprofen, acarbose, lisinopril, ibuprofen, ranitidine, trimethoprim-sulfamethoxazole, vinpocetine, enoxacin, carvedilol and moxonidine GERARD et al 1984;DANHOF et al 1986;KUBACKA et al 1987;SJOEBERG et al 1987;GRANDT et al 1989;GÖBEL et al 1990;MÜLLER et al 1993;HARDER et al 1993). With ranitidine, however, glucose and insulin concentrations are elevated.…”
Section: F) Pharmacokinetic Interactionsmentioning
confidence: 93%
“…The specific transport systems responsible for moxonidine active tubular secretion remain undetermined. It was reported that pharmacokinetics of moxonidine was not altered with coadministration of glibenclamide, which is a known P-glycoprotein inhibitor and substrate (Muller et al, 1993). A recent study also found that quinidine sulfate, a potent inhibitor of organic cation secretion as well as a inhibitor of P-glycoprotein, does not affect the renal clearance of moxonidine (Wise et al, 2002).…”
Section: Moxonidine Metabolism In Humansmentioning
confidence: 98%